Structural evolution of BaCe0.65Zr0.20Y0.15O3-δ-Ce0.85Gd0.15O2-δ composite MPEC membrane by in-situ synchrotron XRD analyses. (September 2019) - Mortalò, Cecilia; Santoru, Antonio; Pistidda, Claudio; Rebollo, Elena; Boaro, Marta; Leonelli, Cristina; Fabrizio, Monica
Abstract: Nowadays, dense ceramic membranes based on mixed ionic and electronic conductors are considered very promising materials for H2 separation at T > 600 °C. Among these, BaCe0.65 Zr0.2 Y0.15 O3-δ -Ce0.85 Gd0.15 O2-δ (BCZ20Y15-GDC15) composite combine an acceptable H2 flux and good chemical stability under CO2 - and H2 S-containing atmospheres. However, a clear understanding of its crystal structure, phase stability and mechanical stability under real working conditions could not yet be obtained. In this work, its structural evolution was investigated from room temperature to 800 °C by in-situ synchrotron XRD analyses under dry and wet H2 . No chemical interaction between the BCZ20Y15 and GDC15 phases occurred in the composite, thus demontrating its excellent chemical stability under operating conditions. However, some phase transitions were observed for the BCZ20Y15 phase, under both dry and wet H2 : i.e., it showed an orthorhombic Imma structure from room temperature to 100 °C, trigonal R-3c up to 700 °C and cubic Pm-3m up to 800 °C. On the other hand, the GDC15 phase did not display any phase transition, remaining in a cubic Fm-3m structure under all tested conditions. Moreover, a synergistic effect of the BCZ20Y15 and GDC15 phases in the volume expansion of the composite was revealed: indeed, BCZ20Y15 and GDC15 lattice expansion rates tend to approach each other in the composite under reducing conditions. This synergistic effect is very important for the mechanical performances of BCZ20Y15-GDC15 composite. The similar expansion rate observed for BCZ20Y15 and GDC15 may reduce the strain and prevent failure of this ceramic membrane under operating conditions. Highlights: Structure evolution of BCZ20Y15-GDC15 under H2 was studied by in-situ synchrotron XRD. An excellent chemical stability was observed up to 800 °C under both dry and wet H2. GDC15 displayed the same cubic Fm-3m structure in all tested conditions. BCZ20Y15 exhibited two transitions: Imma → R-3c at 100 °C and R-3c → Pm-3m at 700 °C. A synergistic effect of BCZ20Y15 and GDC15 observed in the composite volume expansion.